A two-dimensional boundary: Sunnis' perceptions of Alevis. (8th August 2021) - Tuğsuz, Nigar
ABSTRACT: Alevi-Sunni relations in Turkey are the result of a relational process constructed from contributions of each side rather than each groups' perceptions of the other. Boundaries between Alevis and Sunnis in Turkey have been constructed relationally with the contributions of many complicated socio-political factors. This article aims to answer the question of what the symbolic boundaries between the two groups are, seeking to understand how Sunnis perceive Alevis. This aim will cast light on the nature of the two groups' relations, help us recognize forms of Alevism and Sunnism specific to Turkey, and advance existing literature on the issue. This paper's findings are based on ninety semi-structured and two focus group interviews with Sunnis living in Istanbul. Results show that the concept of 'two-dimensional symbolic boundary, ' which runs along dimensions of not-knowing and not-accepting, is the answer to the question of how Sunnis perceive Alevis. The main components of these dimensions are perceptions, which seem to relate to the interpretations of group norms and values. This study, as a group-based analysis, reveals that perceived group norms – whether religious, cultural, social, or political – determine the perceptions of Sunnis towards Alevis and create dimensions of the boundary between the two groups.